Mechanical properties of lithium metasilicate after short-term thermal treatments - Simba, Bruno Galvão [UNESP]; Ribeiro, Marcos Valério [UNESP]; Suzuki, Paulo A.; Alves, Manuel Fellipe R.P.; Strecker, Kurt; Santos, Claudinei dos (Elsevier, 2019)
Objectives: The properties of lithium-silicate dental glass-ceramics are very sensitive to heat treatments which are conducted after CAD/CAM (Computer Aided Design/Computer Aided Machining) processing. In particular, temperature variations inside the furnace chamber which may occur between different models of furnaces may result in altered mechanical properties of these materials. In this work, the effect of thermal treatment parameters on the transformation of lithium metasilicate (Li2SiO3) into lithium disilicate (Li2Si2O5) and on the resulting mechanical properties has been investigated. Methods: Lithium metasilicate samples. containing 59 vol% of amorphous phase, were thermal treated under vacuum at 820 °C for up to 9 min or at 840 °C for 7min (as control group). The samples were characterized by X-ray diffraction analysis using the Rietveld refinement and scanning electron microscopy. Hardness and fracture toughness (n = 30 indentations/group) were evaluated by the Vickers indentation technique. The elastic properties were measured by the Impulse Excitation Technique and the flexural strength (n = 15/group) was measured using the piston-on-three-ball (P–3B) testing assembly. Complementary Weibull statistic were conducted as statistical analysis. Results: The results indicate a progressive reduction of the Li2SiO3 phase with increasing isothermal holding time at 820 °C until the conversion into Li2Si2O5, is completed for treatments longer than 7 min. A complete transformation of Li2SiO3 into Li2Si2O5 has also been observed for the control group of samples treated at 840 °C for 7min. Samples of the control group exhibited hardness, fracture toughness, Young's modulus and Poisson ratio 5.76 ± 0.17 GPa, 1.60 ± 0.03 MPa m1/2, 100.3 GPa e 0.21, respectively. The reduction of the thermal treatment temperature to 820 °C reduced the fracture toughness and the Young's modulus between 5-10%. Furthermore, the fracture strength was significantly reduced by approximately 71%, because of the lower amount of elongated Li2Si2O5 grains and higher amount of residual amorphous phase. Conclusion: In general, the glass-ceramic material containing residual amorphous phase associated with various crystalline phases, presented a reduction of its mechanical properties in relation to the lithium disilicate glass-ceramic. The reasons for these differences in the mechanical behavior are discussed by analyzing the influences of different phenomena such as thermal expansion anisotropy, residual stresses, amorphous phase content and microstructure on the properties.
Keywords: Lithium silicate; Mechanical properties; Microstructure; Thermal treatment; Toughness mechanism